Desire and imitation in international politics - Troy, Jodok (Studies in violence, mimesis, and culture, 2021)
Introduction: International politics and mimetic theory -- International politics and realist thought -- Desire for power and the power of desire -- A realist mimetic view on reconciliation -- Dag Hammarskjöld: international civil service and mimesis -- It's all about competition without shooting each other.